1998
DOI: 10.1159/000027587
|View full text |Cite
|
Sign up to set email alerts
|

A Second Primary Squamous Cell Carcinoma Arising in a Radial Forearm Flap Used for Reconstruction of the Hypopharynx

Abstract: A 63-year-old man had undergone hypopharyngectomy for hypopharyngeal carcinoma in 1985. A free radial forearm flap was used for reconstruction of the pharynx. Ten years after the surgery, a second primary squamous cell carcinoma occurred in the neopharynx. Persistent exposure to alcohol, saliva and foodstuffs was considered as a possible cause of second primary carcinoma. Long-term follow-up is indicated in patients undergoing reconstruction using cutaneous or musculocutaneous flaps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Metaplastic transformation could come from external stimuli, such as saliva or dietary substances. Our case and the cases of Deans et al [7], Scott and Klaassen [8], Sakamoto et al [9] and Iseli et al [10] are all examples of second primary SCC induced by exposure to stimuli that skin does not normally expose. Therefore, prolonged exposure to such non-physiological stimuli for skin could have triggered the neoplastic changes.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Metaplastic transformation could come from external stimuli, such as saliva or dietary substances. Our case and the cases of Deans et al [7], Scott and Klaassen [8], Sakamoto et al [9] and Iseli et al [10] are all examples of second primary SCC induced by exposure to stimuli that skin does not normally expose. Therefore, prolonged exposure to such non-physiological stimuli for skin could have triggered the neoplastic changes.…”
Section: Discussionsupporting
confidence: 56%
“…Scott and Klaassen [8] reported a SCC arising in a pedicle Xap used after mandible resection 40 years ago. Sakamoto et al [9] reported a second primary SCC arising in a radial forearm Xap used for reconstruction of the hypopharynx 10 years after initial operation. Iseli et al [10] also reported a SCC arising in the deltopectoral Xap used for hypopharyngeal reconstruction 27 years afterwards.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our case and the cases of Sakamoto et al 9 Deans et al, 10 Scott and Klaassen, 11 and Johnson et al 12 are all examples of second primary tumors induced by the exposure to stimuli that skin does not normally experience (saliva, dietary substances, and, in some of the other cases, alcohol). In our case, 27 years elapsed between reconstruction and the diagnosis of malignancy in the skin of the flap used to reconstruct the pharynx.…”
Section: Discussionmentioning
confidence: 48%
“…Sakamoto et al 9 reported a second primary squamous cell carcinoma arising in a radial forearm flap used for reconstruction of the hypopharynx 10 years following pharyngolaryngectomy. Deans et al 10 reported late development of squamous cell carcinoma in a deltopectoral skin flap used in pharyngeal reconstruction 24 years following total laryngectomy.…”
Section: Discussionmentioning
confidence: 99%